Reconstruction of laboratory activity design "menyelidiki makanan berkarbohidrat" on digestive system material - Oky Rizkiana Silaban; Bambang Supriatno; Amprasto Amprasto (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Laboratory activities are essential in improving the understanding of learning outcomes and supporting the process of forming students' knowledge about biological material, especially the concept of carbohydrate digestion. It is necessary to laboratory activities design (LAD) that can support forming student knowledge in laboratory activities to investigate carbohydrate foods. This research uses a qualitative descriptive method applied through ANCOR (Analyse, Try, Reconstruct) steps to develop LAD that supports students' knowledge formation process. The ANCOR stages include analysing the sample LAD, conducting trials, and reconstructing it into a new LAD per the Ministry of Education and Culture's learning outcomes. The LAD reconstruction aims to strengthen students' understanding of carbohydrate digestion through laboratory activities emphasizing exploration, direct observation, and active involvement of students in the learning process. It is expected that the use of LAD that has been adjusted will make a significant contribution to improving student learning outcomes in biology materials, improving the learning process in the laboratory, and increasing their understanding of the concept of organ structure and function in the carbohydrate digestive system.Abstrak. Kegiatan laboratorium memegang peranan penting dalam meningkatkan pemahaman, hasil belajar, dan mendukung proses pembentukan pengetahuan siswa. siswa tentang materi biologi, khususnya konsep pencernaan karbohidrat. Perlu Desain Kegiatan Laboratorium (DKL) yang dapat mendukung proses pembentukan pengetahuan siswa pada kegiatan labororatorium menyelidiki makanan berkarbohidrat. Penelitian ini menggunakan metode deskriptif kualitatif yang diterapkan melalui langkah-langkah ANCOR (Analisis, Coba, Rekonstruksi) untuk mengembangkan DKL yang mendukung proses pembentukan pengetahuan siswa. Tahapan ANCOR tersebut meliputi analisis DKL sampel, melakukan uji coba, dan merekonstruksi menjadi DKL yang baru yang sesuai dengan capaian pembelajaran Kemendikbud. Rekonstruksi DKL bertujuan untuk memperkuat pemahaman siswa terhadap konsep pencernaan karbohidrat melalui kegiatan laboratorium yang menekankan eksplorasi, pengamatan langsung, dan keterlibatan aktif siswa dalam proses pembelajaran. Diharapkan penggunaan DKL yang telah disesuaikan akan memberikan kontribusi yang signifikan dalam meningkatkan hasil belajar siswa dalam materi biologi, memperbaiki proses pembelajaran di laboratorium, serta meningkatkan pemahaman mereka tentang konsep struktur organ dan fungsinya pada sistem pencernaan karbohidrat.